Deep Brain Stimulation Effects on Gait Pattern in Advanced Parkinson’s Disease Patients - Navratilova, Daniela; Krobot, Alois; Otruba, Pavel; Nevrly, Martin; Krahulik, David; Kolar, Petr; Kolarova, Barbora; Kaiserova, Michaela; Mensikova, Katerina; Vastik, Miroslav; Kurcova, Sandra; Kanovsky, Petr (Frontiers in Neuroscience, 2020)
Background: Gait disturbance accompanies many neurodegenerative diseases; it is characteristic for Parkinson’s disease (PD). Treatment of advanced PD often includes deep brain stimulation (DBS) of the subthalamic nuclueus. Regarding gait, previous studies have reported non-significant or conflicting results, possibly related to methodological limitations. Objective: The objective of this prospective study was to assess the effects of DBS on biomechanical parameters of gait in patients with PD. Methods: Twenty one patients with advanced PD participated in this prospective study. Gait was examined in all patients using the Zebris FDM-T pressure-sensitive treadmill (Isny, Germany) before DBS implantation and after surgery both immediately, further immediately after the start of neurostimulation and three months after neurostimulator activation. We assessed spontaneous gait on a moving treadmill at different speeds. Step length, stance phase of both lower limbs, double stance phase and cadence were evaluated. Results: In this study, step length increased, allowing the cadence to decrease. Double stance phase duration i.e., the most sensitive parameter of gait quality and unsteadiness, was reduced, in gait at a speed of 4.5 km/h and in the narrow-based gaits at 1 km/h (tandem gait), which demonstrates improvement. Conclusion: This study suggests positive effects of DBS treatment on gait in PD patients. Improvement was observed in several biomechanical parameters of gait.